Exploring the Impact of Game-Based Learning on English Language Proficiency: Student Engagement, Educator Perceptions, and Implementation Challenges - Henriques; Oliveira (International Journal of Curriculum Development, Teaching and Learning Innovation, 2024)
This research explores the impact of game-based learning on English language proficiency, student engagement, educator perceptions, and implementation challenges. Through a mixed-methods approach, including pre- and post-intervention language assessments, interviews, and focus group discussions, the study investigates the effectiveness of game-based pedagogy in enhancing language learning outcomes. Quantitative analysis of assessment scores reveals significant improvements in both receptive and productive language skills among participants engaged in game-based learning activities. Qualitative data illuminate heightened levels of student engagement and motivation, as well as positive perceptions of game-based pedagogy among educators. However, challenges such as inequities in access to technology resources and the need for professional development for educators are identified. The findings underscore the transformative potential of game-based learning in fostering English language proficiency and inform theory, practice, and policy in language education. By leveraging these insights, stakeholders can work collaboratively to enhance language learning outcomes and promote innovation and inclusivity in English language education.